Rahmah Prepaid Siswa Package benefits UMPSA students - Mimi Rabita, Abd Wahit (UMPSA, 2024)
PEKAN, 19 July 2024 - Students at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) are welcoming the Ministry of Communications' recent announcement of the Rahmah Prepaid Siswa Package.